(untitled) (Acta Scientiarum. Animal Sciences, 2020)
This research was aimed to evaluate the effect of dietary supplementation of either powdered or encapsulated probiotic on relative carcass, giblet weight and intestinal morphometry of local duck. One hundred twenty male day old duck (DOD) were distributed to 6 different dietary groups, included 2 probiotic forms of either powdered (T1) or encapsulated (T2) and 3 levels: 0% (L0), 0.2% (L1), 0.4% (L2). They were reared using pen cages for 42 days (6 weeks). Observed variables were relative carcass, giblet weight (gizzard, heart, liver) and intestinal morphometry (villus height, villus width, crypt depth). Data were analyzed by Nested of Completely Randomized Design ANOVA and if there was significant effect followed by Duncan’s Multiple Range Test (DMRT). The result showed that there was no significant effect (p > 0.05) of the form of either powdered or encapsulated probiotic on relative carcass, giblet weight, and intestinal morphometry. However, increasing level of probiotic have significant effect (p < 0.05) on relative carcass, villus height, and villus width, but did not significantly affect giblet weight and crypt depth. In conclusion, supplementation of either powdered or encapsulated probiotic has similar result, but it is suggested to use 0.4% of encapsulated probiotic (4 kg ton-1 of feed) in local duck diet.